SME's Intention to Use Paid Online Ad: The Theory of Planned Behavior Approach - Ichsana, Yera; Aina, Qorri (Journal of Business and Management, 2020)
Abstract. The purpose of this study is to find out and describe in general how extent the influence of attitudes, subjective norms, and perceived behavioral control of the intention of Small and Medium Enterprises (SMEs) in using paid online advertising. The analysis technique used in this study is by look at the significance of the data that has been filled in by respondents both partially and simultaneously. The subjects of this study were SME owners who were operational and had used e- commerce platforms in Bandung with 90 respondents. Furthermore, researchers use non-probability sampling in the sampling technique with the type of convenience to make it easier for researchers to get a sample. The results of this study indicate that the level of significance both partially and simultaneously shows that attitudes, subjective norms, and perceived behavioral control have a positive and significant effect on the interests of SME owners to use paid online advertising.Keywords: SME’s Intention, The Theory of Planned Behavior, Paid Online Ad, Attitudes, Subjective Norms, Perceived Behavioral Control